Arahan Pencegahan Bahaya Kebakaran di Kawasan Permukiman Penduduk Kelurahan Banta-Bantaeng, Kota Makassar - Muhammad Naufal Hadyan; Wiwik Wahidah Osman; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
The development of a city cannot be separated from the population that always increases every year. With the increase in population growth in a city, the problems that arise will also increase, such as a fire disaster caused by human negligence itself. This study aims to (1) identify the characteristics of settlements and residents against the risk of fire disasters located in Banta-Bantaeng village; (2) identify the availability of facilities and infrastructure to support firefighter activities in residents located in Banta-Bantaeng village; and (3) explaining direction on preventing fire hazards in residential areas. This research located in RW 001, 004, and 005, Banta-Bantaeng Village, Makassar City. The analytical technique used in this research is descriptive qualitative analysis, comparative analysis, and spatial analysis. The results obtained are; (1) the characteristics of the settlements, indicates locations that are prone to fire; (2) the availability of infrastructure is still very less than they can hinder the extinguishing process; and (3) the right direction for preventing fire hazards to overcome fire disasters is by means of active protection, passive protection, and fire safety management.